Androgen receptor–mediated assisted loading of the glucocorticoid receptor modulates transcriptional responses in prostate cancer cells - Hiltunen, Johannes; Helminen, Laura; Aaltonen, Niina; Launonen, Kaisa-Mari; Laakso, Hanna; Malinen, Marjo; Niskanen, Einari A.; Palvimo, Jorma J.; Paakinaho, Ville

(untitled) (Genome Research, 2025)
Steroid receptors are involved in a wide array of cross talk mechanisms that regulate diverse biological processes, with significant implications in diseases, particularly in cancers. In prostate cancer, indirect cross talk between androgen receptor (AR) and glucocorticoid receptor NR3C1 (also known as GR) is well documented, wherein AR suppression by antiandrogen therapy leads to elevated GR levels, enabling GR to compensate for and replace AR signaling. However, the existence and impact of direct chromatin cross talk between AR and GR in prostate cancer have remained elusive. Here, our genome-wide investigations reveal that AR activation significantly expands GR chromatin binding. Mechanistically, AR induces remodeling of closed chromatin sites, facilitating GR binding to inaccessible sites. Importantly, coactivation of AR and GR results in distinct transcriptional responses at both the cell population and single-cell levels. Pathways affected by these transcriptional changes are generally associated with improved patient survival. Thus, the direct cross talk between AR and GR yields markedly different outcomes from the known role of GR in circumventing AR blockade by antiandrogens.